Anatomical study of the medial branches of the lumbar dorsal rami: implications for image-guided intervention. Issue 8 (19th May 2022) - Tran, John; Peng, Philip; Loh, Eldon
Abstract : Introduction: Fluoroscopic-guided radiofrequency ablation of the lumbar medial branches is commonly performed to manage chronic low back pain originating from the facet joints. A detailed understanding of the course of medial branches in relation to bony and soft tissue landmarks is paramount to optimizing lumbar denervation procedures, particularly parallel placement of the radiofrequency electrode. The objectives of this study were to investigate the relationship of medial branches to anatomical landmarks and discuss the implications for lumbar denervation. Methods: Ten cadaveric specimens were meticulously dissected. The origin, course, and relationship of lumbar medial branches to bony and soft tissue landmarks were documented. Results: The medial branches followed the lateral neck of superior articular process deep to the intertransversarii mediales muscle at each lumbar vertebral level. In all specimens, the medial branches coursed laterally on the anterior half of the neck and transitioned from parasagittal-to-medial on the posterior half to reach the mamillo-accessory notch. The mamillo-accessory ligament was found to not occlude the nerve on the posterior quarter of the lateral neck but rather at the mamillo-accessory notch located at the posterior margin of the superior articular process. Discussion: A detailed understanding of the relationship of medial branches to anatomical landmarks is essential to optimizing needle placement for lumbar denervation procedures. The current study suggests that a parasagittal placement, with increased cranial-to-caudal angulation of the electrode, may improve parallel tip alignment with the targeted medial branch and represent a potential alternative to the traditional technique.